Productivity and Vigor Dynamics in a Comparative Trial of Hedgerow Olive Cultivars - Juan Manuel Pérez-Rodríguez; Raúl De la Rosa; Lorenzo León; Encarnación Lara; Henar Prieto (Agriculture, 2024)
The hedgerow growing system is prevalent in new olive orchards worldwide due to its fully mechanized harvesting. Several works have been published to compare cultivars planted in this system, focusing on productivity and oil composition. However, little research has been conducted on the long-term evaluation of cultivars’ growth habits when trained in hedgerow systems and on how it affects their interannual productivity. In this work, we report the canopy growth habit, productivity, and their correlation for the ‘Arbequina’, ‘Arbosana’, ‘Koroneiki’, ‘Lecciana’, ‘Oliana’, and ‘Sikitita’ cultivars grown in a hedgerow system in Extremadura, central-western Spain, for 9 years. ‘Koroneiki’, ‘Arbequina’, and ‘Lecciana’ were the cultivars with the highest canopy growth, both in young and adult trees, and the ones with the highest pruning needs from 5 to 10 years after planting. The yield behavior in each of the years evaluated was stable in all cultivars except ‘Lecciana’. This alternate bearing was associated with the distribution of total yearly produced biomass between fruits and vegetative growth. ‘Oliana’, ‘Arbosana’, and ‘Sikitita’ were the cultivars with the highest proportion of fruit of the total biomass, and ‘Lecciana’ showed the lowest. This study indicates that cultivars with higher fruit proportions of total biomass might have better suitability for long-term growing in hedgerow formation, fewer pruning needs, and more stable productivity across the years. In this sense, in the climatic conditions considered here, ‘Arbosana’, ‘Sikitita’, and ‘Oliana’ could be the most suitable cultivars for this growing system.